2006
DOI: 10.1128/ec.00244-06
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione Reductase and a Mitochondrial Thioredoxin Play Overlapping Roles in Maintaining Iron-Sulfur Enzymes in Fission Yeast

Abstract: In the fission yeast Schizosaccharomyces pombe, the pgr1 ؉ gene encoding glutathione (GSH) reductase (GR) is essentially required for cell survival. Depletion of GR caused proliferation arrest at the G 1 phase of the cell cycle under aerobic conditions. Multicopy suppressors that restore growth were screened, and one effective suppressor was found to be the trx2 ؉ gene, encoding a mitochondrial thioredoxin. This suggests that GR is critically required for some mitochondrial function(s). We found that GR reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 57 publications
(78 reference statements)
0
44
0
Order By: Relevance
“…These results indicated that the first methionine and Met 86 are responsible for GlrA localization in the mitochondria and cytosol, respectively, and that the 85 amino acid residues before Met 86 target GlrA into the mitochondria. Both cytosolic and mitochondrial localizations of A. nidulans GR are similar to the GR of S. cerevisiae and of S. pombe, which produce both mitochondrial and cytosolic GR from two translation initiation sites (10,36). However, the activity of the mitochondrial GR differed in that A. nidulans produced considerably less of it than S. cerevisiae, which produces ϳ35% more activity mg protein Ϫ1 in the mitochondria than in the cytosol (36).…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…These results indicated that the first methionine and Met 86 are responsible for GlrA localization in the mitochondria and cytosol, respectively, and that the 85 amino acid residues before Met 86 target GlrA into the mitochondria. Both cytosolic and mitochondrial localizations of A. nidulans GR are similar to the GR of S. cerevisiae and of S. pombe, which produce both mitochondrial and cytosolic GR from two translation initiation sites (10,36). However, the activity of the mitochondrial GR differed in that A. nidulans produced considerably less of it than S. cerevisiae, which produces ϳ35% more activity mg protein Ϫ1 in the mitochondria than in the cytosol (36).…”
Section: Resultsmentioning
confidence: 78%
“…We showed that exogenous oxidants induced glrA expression and inhibited cell growth and conidial germination more effectively in the DGR1 than in the wild type strain, indicating that GR (or GSH) functions as an antioxidant in A. nidulans as it does in yeasts and other organisms (7)(8)(9)(10). Menadione was the most powerful inducer of glrA expression among the tested oxidants.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations